2014
DOI: 10.1016/j.jesp.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

How ideological migration geographically segregates groups

Abstract: Here, we advance the ideological migration hypothesis -individuals choose to live in communities with ideologies similar to their own to satisfy their need to belong. In Study 1, incongruity between personal and community ideology predicted greater residential mobility and attraction to more ideologically-congruent communities. In Study 2, participants who perceived their ideology to be at odds with their community's displayed a decreased sense of belonging and an increased desire to migrate. In Studies 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(177 citation statements)
references
References 102 publications
5
172
0
Order By: Relevance
“…For example, people with particular ideal partner preferences may be more likely to seek out social contexts where potential mates with qualities similar to their preferences are also likely to frequent. Indeed, research by Motyl, Iyer, Oishi, Trawalter and Nosek [22] has demonstrated that individuals select communities with ideologies similar to their own in which to live. Individuals that ideally prefer someone who likes being physically active may therefore be particularly likely to meet a future partner while mutually engaging in these types of activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, people with particular ideal partner preferences may be more likely to seek out social contexts where potential mates with qualities similar to their preferences are also likely to frequent. Indeed, research by Motyl, Iyer, Oishi, Trawalter and Nosek [22] has demonstrated that individuals select communities with ideologies similar to their own in which to live. Individuals that ideally prefer someone who likes being physically active may therefore be particularly likely to meet a future partner while mutually engaging in these types of activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent survey data suggests that lesbian, gay, bisexual, and transgender (LGBT) individuals report feeling stigmatized and they do not belong in red states where the majority of the population has supported banning same-sex marriage and forbidding non-heterosexuals from teaching in public schools (Lick, Tornello, Riskind, Schmidt, & Patterson, 2012). This sense of not belonging triggers selective migration to places where people feel that they are accepted and that they do belong (Motyl, 2014;Motyl et al, 2014). Some evidence even suggests that LGBT individuals may be fleeing red communities and heading for greener (or, more rainbow-patterned) pastures Smart & Klein, 2013).…”
Section: Liberals and Conservatives Are (Geographically) Dividingmentioning
confidence: 99%
“…Modern humans migrate for these reasons, but for many others, too. People consider the activities differe nt residences would permit, the proximity to (or distance from) family members, the availability of desirable occupations, and whether they would feel a sense of belonging in those communities (Motyl, 2014;Motyl, Iyer, Oishi, Trawalter, & Nosek, 2014). It is this pursuit of belonging that may lead to the emergence of increasingly ideologically-and morally-homogeneous enclaves.…”
Section: Intuitions Steer Selective Migration Into Ideological Enclavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on the ideological migration hypothesis supported these assumptions. Several studies showed that people selectively migrate away from communities that do not fit their ideological worldviews but choose destinations that provide a better fit (Motyl, Iyer, Oishi, Trawalter, & Nosek, 2014). However, we are not aware of any studies that investigated selective migration by Big Five traits constellations, suggesting interesting objectives for future research.…”
Section: The Interplay Of Personality Environments and Mobility At mentioning
confidence: 89%